The disembodiment of birthing and the incapacity to theologically reflect: a perspective from perinatal mental illness in ministry - Allison-Glenny, Elizabeth (Practical theology, 2023)
This paper offers an autoethnographic account of perinatal mental illness in ministry, exploring how this impacted the ability to theologically reflect. It explores theological reflection as an embodied activity, described in procreative language. In particular, it stresses the prestige theological reflection is given in Baptist ministry as a tool for encountering difficulty, and how the inability to do so in the moment of crisis created a heightened sense of loss.